FACTORS ASSOCIATED WITH COMMON MENTAL DISORDERS AMONG WOMEN OF REPRODUCTIVE AGE IN SUMAILA LOCAL GOVERNMENT AREA, KANO STATE - Haddad, M. M.; Ojukwu, A. I.; Mansur, B. Y.; Yunusa, U.; Umar, B. L.; Bilkisu, U. B.; Murtala, H. H.; Muhammad, U. I. (FUDMA Journal of Sciences, 2020)
The study was conducted to evaluate the factors associated with common mental disorders among women of reproductive age in Sumaila Local Government Area of Kano state. Cross-sectional descriptive design was used. A total of 163 women were recruited for the study using multi-stage sampling technique. A close-ended structured questionnaire was used for data collection. Data collected were organized and analyzed with Statistical Package for the Social Sciences (SPSS) version 20.0 and results were presented using frequency distribution and percentages, and meanÂ±standard deviation. Chi-square analysis was used to test for association between factors associated with and development of common mental disorders at 5% level of significant within 95% confidence interval. Findings from the study revealed that 28.4% of the respondents had Common Mental Disorders, awareness of the respondents were low as most of them believed that demonic possession (73.5%) and witchcraft (58.6%) were the causes of mental illness.   Significant association was found between factors associated with common mental disorders and age at first marriage (Ï‡2=3.395, p=0.048) and low social integration (Ï‡2=5.414, p=0.020), of the women.  The study concluded that common mental disorders in rural communities are mostly related to age at first marriage   It is recommended that mental health personnel should conduct advocacy to traditional and religious leaders, also the male parents in rural areas on the influence of early marriage on mental disorders and clear their misconceptions on its causes, for early prevention and improved mental health seeking behaviour.
Keywords: Awareness; Common mental disorders; Factors; Rural community; Women of reproductive age